Spatial analysis on Malay buildings for categorization of Malay historic BIM library - Mustafa, Muhammad Hadi; Ali, Maisarah; Mohd Ismail, Kamsiah; Hashim, Khairusy Syakirin Has-Yun; Mohamad Suhaimi, Mohamad Saifulnizam (2019)
Problem statement/Literature Review: In Malaysia, Malay cultural architecture is becoming a popular topic since Malay architecture is believed to have unique characteristics, which would be beneficial if translated into BIM environment. However, a BIM library needs a localized system and categorization for its interface since a cultural heritage library should reflect their own original identity of architecture. From literature, it was found that the traditional design form in Malay architecture can be identified through several aspects that are inherent physical elements in the design which can be sorted into five distinct categories which are (i) Structural members (ii) Non-structural members (iii) Aesthetic and decorative elements (iv) Spatial composition and organization and (v) Material and construction technology. Methodology: In order to develop a BIM library with cultural identity, this paper further the study on the characters of Malay architecture based on the spatial composition and organization aspect with respect to the theory of space and taxonomy. Results & Analysis: A spatial analysis on the layout of multiple historic Malay buildings consisting of commoners’ house and palaces were conducted where the naming of areas within the building zones was identified and presented to propose a novel categorization structure for Malay Historic BIM library. Conclusion: This study proposed an approach on how to address the issue of developing a BIM library based on the cultural architecture characters.